Characterization of aerodynamic performance of ducted wind turbines: A numerical study. Issue 12 (8th October 2019) - Dighe, Vinit V.; de Oliveira, Gael; Avallone, Francesco; van Bussel, Gerard J. W.
Abstract: The complex aerodynamic interactions between the rotor and the duct has to be accounted for the design of ducted wind turbines (DWTs). A numerical study to investigate the characteristics of flow around the DWT using a simplified duct–actuator disc (AD) model is carried out. Inviscid and viscous flow calculations are performed to understand the effects of the duct shape and variable AD loadings on the aerodynamic performance coefficients. The analysis shows that the overall aerodynamic performance of the DWT can be increased by increasing the duct cross‐sectional camber. Finally, flow fields using viscous calculations are examined to interpret the effects of inner duct wall flow separation on the overall DWT performance.